Implications of Rescheduling the Direct Election of The Regional Head (PILKADA) of South Sumatra in The Midst of The Covid-19 Pandemic - Redi Pirmansyah; Junaidi Junaidi; Martindo Merta (UIN Sunan Gunung Djati, 2022)
Based on Article 201 paragraph (6) of Law Number 10 of 2016, Indonesia has an agenda to hold the General Election for Regional Heads (Pilkada) on September 23, 2020. This Covid-19 pandemic period has caused simultaneous Regional Head elections (Pilkada) in seven districts and cities in South Sumatra (Sumsel) were officially postponed, this delay was due to the corona virus outbreak or Covid-19. The purpose of this study is to explain, analyze and find laws in providing alternatives for filling regional head positions during the Covid-19 pandemic. The research method uses empirical juridical (field research), namely examining the applicable legal provisions and what is happening in reality in society. The results show several alternative patterns of filling regional head positions during the Covid-19 pandemic, including through the appointment of a temporary acting or task executor (Plt), indirect elections, and elections using the electronic election system. Each pattern has its advantages and disadvantages, with strong logical and juridical arguments that can be taken into consideration.